Reinterpreting Millenarian Sentiments at the Dutch Cape Colony: The Incredulous Colonial Responses to the Khoikhoi Uprising of 1788 and the Religiously Syncretic Longing for an Apocalypse - van der Wal, Anne Marieke (BMGN - Low Countries Historical Review, 2023)
During the long nineteenth century, European colonists, in among others Asia and Africa, were often confronted with self-proclaimed prophets who predicted an apocalyptic uprising which would bring about a new era of peace and independence from European control. The Dutch colonial world has known several of such ‘prophets of rebellion’, as millenarian beliefs flourished particularly in times of distress. This article focuses on the Khoikhoi uprising of 1788 and their revealed prophet the ‘liewe heer’ Jan Paerl, in the Dutch Cape Colony, and seeks to break with patterns in the current study of apocalyptic prophecies and messianic, anticolonial uprisings that approaches these phenomena from a religious radicalisation perspective. Instead, this article aims to reassess whether the religious dimension of this uprising was indeed seen as the most threatening to Dutch colonial authorities at the time, as well as the most appealing and convincing component for its followers.